MODIFIED COUPLED-INDUCTOR SINGLE-STAGE BOOST INVERTER BASED GRID-CONNECTED PHOTOVOLTAIC (PV) SYSTEM - Mr.Mohasin Shafiahamad Bijali.; Prof. MallaReddy Chinala; Prof. Anitha Chirra (International Journal of Innovations in Engineering Research and Technology, 2021)
Grid connected Photovoltaic(PV) Power System has been attracting more and more attention for its lower cost, smaller volume, as well as higher efficiency. One of the technical challenges is the safety issue of the leakage current caused by the common mode voltages(CMV)conducting in the loop with parasitic capacitorsbetween the solar panel and the ground. A coupled inductor single stage boost inverter (CL-SSBI) will be introduce an impedance network, including coupled inductor in the front end of inverter bridge. Usingcoupled inductor single stage boost inverter (CL-SSBI) with near state pulse width modulation(NSPWM) which can reduce leakage current of the grid connected PV system. The proposed transformer less grid connected photovoltaic (PV) system on the CL-SSBI modulated by NSPWM will be simulated in MATLAB/SIMULINK.